Influences of race/ethnicity in periodontal treatment response and bacterial distribution, a cohort pilot study - Wang, Bing-Yan; Burgardt, Grayson; Parthasarathy, Kavitha; Ho, Daniel K.; Weltman, Robin L.; Tribble, Gena D.; Hong, Jianming; Cron, Stanley; Xie, Hua (Frontiers in Oral Health, 2023)
OBJECTIVES: Periodontitis disproportionately affects different racial and ethnic populations. We have previously reported the higher levels of Porphyromonas gingivalis and lower ratios of Streptococcus cristatus to P. gingivalis may contribute to periodontal health disparities. This prospective cohort study was designed to investigate if ethnic/racial groups responded differently to non-surgical periodontal treatment and if the treatment outcomes correlated to the bacterial distribution before treatment in patients with periodontitis before treatment. METHODS: This prospective cohort pilot study was carried out in an academic setting, at the School of Dentistry, University of Texas Health Science Center at Houston. Dental plaque was collected from a total of 75 African Americans, Caucasians and Hispanics periodontitis patients with different ethnic/racial background – African Americans, Caucasians and Hispanicsin a 3-year period. Quantitation of Porphyromonas P. gingivalis and Streptococcus S. cristatus was carried out using qPCR. Clinical parameters including probing depths and clinical attachment levels were determined before and after nonsurgical treatment. Data were analyzed using one-way ANOVA, the Kruskal-Wallis test, the paired samples t-test and the chi-square test. RESULTS: The gains in clinical attachment levels after treatment significantly differed amongst the 3 groups – Caucasians responded most favorably, followed by African-Americans, lastly Hispanics, while numbers of P. gingivalis were highest in Hispanics, followed by African-Americans, and lowest in Caucasians (p = 0.0151). However, no statistical differences were found in the numbers of S. cristatus amongst the 3 groups. CONCLUSION: Disparities inDifferential response to nonsurgical periodontal treatment and distribution of P. gingivalis are present in different ethnic/racial groups with periodontitis.